2019
DOI: 10.1038/s41598-019-51804-7
|View full text |Cite
|
Sign up to set email alerts
|

Environmental fungi and bacteria facilitate lecithin decomposition and the transformation of phosphorus to apatite

Abstract: Organophosphorus compounds (OP) are stable P source in nature, and can increase eutrophication risk in waterbodies. Lecithin was the most difficult OP to be broken down. In this study, two typical phosphate-solubilizing microorganisms, Aspergillus niger and Acinetobacter sp., were applied to evaluate their ability to decompose both inorganic phosphates and lecithin. A. niger and Acinetobacter sp. could solubilize calcium phosphates by secreting various organic acids, e.g., oxalic and formic acids. The fungus, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Generally, in acidic soils, P ions tend to precipitate with Fe and Al cations to form insoluble oxyhydroxides or secondary P i minerals. In alkaline soils, P ions mainly precipitate with Ca to form secondary P i minerals, such as fluroapatite, hydroxyapatite, and chloroapatite [ 101 , 102 , 103 ]. Thus, the geochemical precipitation of P in soil and wastewater have contrasting effects on physicochemical stabilization of organic P compounds and environmental control of P i levels [ 44 , 104 , 105 ].…”
Section: Psm-induced Dissolution In Accelerating Metal Precipitatimentioning
confidence: 99%
“…Generally, in acidic soils, P ions tend to precipitate with Fe and Al cations to form insoluble oxyhydroxides or secondary P i minerals. In alkaline soils, P ions mainly precipitate with Ca to form secondary P i minerals, such as fluroapatite, hydroxyapatite, and chloroapatite [ 101 , 102 , 103 ]. Thus, the geochemical precipitation of P in soil and wastewater have contrasting effects on physicochemical stabilization of organic P compounds and environmental control of P i levels [ 44 , 104 , 105 ].…”
Section: Psm-induced Dissolution In Accelerating Metal Precipitatimentioning
confidence: 99%
“…In the paper [94] was found that Acinetobacter sp. CGMCC 13078 is capable of solubilizing both inorganic and organic phosphates.…”
Section: Ability Of Acinetobacter Bacteria To Phosphates Solubilization and Xenobiotics Degradationmentioning
confidence: 99%
“…Phosphate mobilizing. Phosphate-solubilizing rhizobacteria (PSRB) improve soil fertility by converting insoluble forms of phosphorus to soluble plant-available forms [93,94]. The source of PSRB isolation is soils that are deficient in soluble phosphates.…”
Section: Ability Of Acinetobacter Bacteria To Phosphates Solubilization and Xenobiotics Degradationmentioning
confidence: 99%
See 2 more Smart Citations